TRATAMENTO DE RESÍDUOS ORGÂNICOS DOMÉSTICOS E DE DEJETOS BOVINOS POR MEIO DA VERMICOMPOSTAGEM - MARTINS, Gabriel da Silva; WOICIECHOWSKI, Thiago; PIGARI, Hugo Pereira; SALMAZZO, Gustavo Ruivo (ANAIS DO ENIC, 2023)
-